2019
DOI: 10.1177/2050640619860965
|View full text |Cite
|
Sign up to set email alerts
|

Beclomethasone dipropionate in microscopic colitis: Results of an exploratory open‐label multicentre study (COLCO)

Abstract: Background: Budesonide has been proven to be an effective treatment for microscopic colitis (MC). However, the two current commercially available preparations are released in the ileum. Beclomethasone dipropionate (Clipper Õ ) is a synthetic corticosteroid with topical colonic release.Objective: This study aimed to explore whether an open-label treatment with beclomethasone dipropionate is an effective treatment for MC. Methods: Prospectively collected data of 30 patients from six centres were retrospectively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 23 publications
(82 reference statements)
2
8
0
Order By: Relevance
“…This series more than doubles the reported experience of beclometasone dipropionate in microscopic colitis and confirms the overall efficacy and safety. Results are comparable to the small series reported by Corte et al (remission 70%) 1 and Latella et al (remission 83%), 2 although in the latter study, the remission rate in the mesalazine‐treated group (13/15; 86%) was strikingly high, given that other studies have consistently shown that mesalazine is inferior to ileal‐release budesonide 4 , 5 . Colonic‐release formulations are a logical treatment for a disease that typically affects all segments of the colon.…”
supporting
confidence: 91%
See 3 more Smart Citations
“…This series more than doubles the reported experience of beclometasone dipropionate in microscopic colitis and confirms the overall efficacy and safety. Results are comparable to the small series reported by Corte et al (remission 70%) 1 and Latella et al (remission 83%), 2 although in the latter study, the remission rate in the mesalazine‐treated group (13/15; 86%) was strikingly high, given that other studies have consistently shown that mesalazine is inferior to ileal‐release budesonide 4 , 5 . Colonic‐release formulations are a logical treatment for a disease that typically affects all segments of the colon.…”
supporting
confidence: 91%
“…Results are comparable to the small series reported by Corte et al. (remission 70%) 1 and Latella et al. (remission 83%), 2 although in the latter study, the remission rate in the mesalazine-treated group (13/15; 86%) was strikingly high, given that other studies have consistently shown that mesalazine is inferior to ileal-release budesonide.…”
supporting
confidence: 86%
See 2 more Smart Citations
“…170,173,288,311,312 An open-label retrospective study investigated beclomethasone dipropionate as a synthetic corticosteroid with topical colonic release in 30 patients with MC showing a response rate of 80% and remission rate of 67%. 313 Is there a role for immunomodulators and biologics in the treatment of patients with MC?…”
Section: Diagnosis Of MC What Is the Endoscopic Appearance Of Mc?mentioning
confidence: 99%